Growing as an Indonesian Ursuline Together with Muslim Friends - Wiguno, Nurhayati, OSU (Archīum Ateneo, 2024)
The author's beautiful childhood experience in the dialogue of life, spiritual experience, and cooperation with Muslim friends became a strong foundation when choosing to live in a convent, where she must live 24 hours a day continuously with other Sisters of different backgrounds, cultures, ethnicities, and nationalities. Saint Angela's charism of siete piazzevole, the twofold of love, and contemplation in action can be a strength in realizing the Ursuline Mission to engage in dialogue to find new breakthroughs that can make us neighbors to others.